(untitled) (Research, Society and Development, 2020)
This experience report aims to reflect on the theme of Mental Health in the context of Primary Care experienced by the team of the Project PET-Health/Interprofessionality. It is an exploratory-descriptive research with a qualitative approach. Data collection occurred through the technique of participatory observation through the report of the experience of a group PET at the University of the State of Minas Gerais (UEMG), in health units, with the teams of the Family Health Strategy, between january and july 2019, through a survey of the difficulties faced by the professionals of the primary care. Academics and professors from the Nursing, Medicine and Social Work courses and professionals already included in the health context participated in the project. The difficulties identified were organized into three groups, namely: professionals and reference services of mental health; functioning of the psychosocial care network and mental health users.